(untitled) (Journal of Libya for geographical studies, 2024)
The study dealt with the demographic dimensions of the Italian occupation of Libya. The study aimed to identify the impact of wars on population growth and to know the change in the size of the population in the country and at the level of the three historical regions, and also to know the demographic colonial policy that Italy followed in the settlement operations. The study followed the historical approach and the descriptive analytical approach. The quantitative method to explain the phenomenon is under study, and I concluded that Italian colonialism had negative effects on the Libyan population, as it hindered its development and contributed to its demographic delay. It also explained that there is a regional disparity in the development of population size between the regions, and that the regions of Tripoli and Fezzan were slowly increasing. While Cyrenaica had the lion’s share of this negative impact on the development of its population mass due to the continuation and length of the resistance period, which made its mass decline demographically and recorded a negative population decline that reached its peak during the period (1923-1929), recording about (-40,000) people, and the population growth rate reached about 1.04%, for the period (1911-1931), while the rate rose to record about 3.6% for the period (1954-1964). It was also shown that due to the colonial demographic policy, the numbers of Italian settlers developed and their numbers rose from about 19 thousand people in 1921 to about 115 thousand people in the year. 1936, to constitute about 13.6% of the total population, and then their numbers rose to 122 in 1940. The Italian occupation contributed to the imbalance in the gender ratio among the younger groups of the population, and the most imbalanced of these age groups is the age group (20-24) years.